Therapeutic Architecture Based on Environmental Analysis in Healthcare Facility Design in Surabaya - Kansa Agnesia; Mufidah; Suko Istijanto (Kirana Publisher (KNPub), 2026)
Rapid urbanization in Surabaya has intensified environmental pressures, reduced green open spaces, and increased stress levels among urban populations, highlighting the urgent need for healthcare environments that support both physical recovery and psychological well-being. In this context, therapeutic architecture offers a promising approach by integrating natural elements into spatial design to enhance healing experiences. This study aims to investigate the role of site analysis as a fundamental basis for designing holistic healthcare facilities based on therapeutic architecture, focusing on a site located at Jalan Kalisari Permai I,Mulyorejo District, Surabaya. The site is characterized by a relatively quiet residential environment, adequate accessibility, and the presence of existing vegetation with favorable microclimatic conditions. A qualitative descriptive method with a design-based research approach was employed, combining field observations, literature review, and environmental analysis. Key site parameters include solar orientation, wind patterns, noise levels, accessibility, vegetation, visual quality, and microclimate. The findings reveal that site characteristics play a critical role in shaping therapeutic design strategies. Variations in noise levels (74 dB at the front, 58 dB in the middle, and 49 dB at the rear) inform a layered zoning system from public to private spaces. Solar exposure analysis highlights the need for heat control on the western side and daylight optimization on the eastern and northern sides. Dominant east–west wind patterns support cross-ventilation strategies, while existing vegetation enhances thermal comfort and contributes to a restorative healing environment. The implementation of therapeutic architecture is realized through hierarchical spatial zoning, passive environmental design strategies, and the integration of a healing garden as a central design element. This study contributes to bridging the gap between site analysis and architectural design by demonstrating how environmental parameters can be systematically translated into spatial strategies for holistic healthcare facilities. The findings provide a context-responsive design framework applicable to urban healthcare environments in tropical regions.